Fighting the Information Forgery Crime in the Light of the Comparative Laws - Wahaib, Moshtaq Talib (Journal of Legal Sciences, 2021)
Legislation may be often not enough for protecting information, and regulatory strategies are insufficient as well. Technical means are not also sufficient in preventing risks threating information whatever their effectiveness is. Thus, the protection is a complex structure consisting of law, regulation strategy and technology. The increasing use of and reliance on computer information systems has highlighted the need for good information system management. Legislative control can have a positive effect on this system by providing deterrence and increasing the public awareness of users about the problem.Consequently, it is required looking for legislative means at the time in which the fight is more effective against this kind of criminality, and creating a safe environment and regulated according to legislations providing an acceptable amount of the protection of information circulated within the range of the technological society through making a comparative study of some legislations in order to establish a common ground if we want to find effectively legislative fight.